Processed physical properties measured on sediment core MSM31_561-2_GKG - Andrea Catalina Gebhardt (PANGAEA, 2025)
Sound knowledge about the petrophysical characteristics of a sediment core is a prerequisite for any subsequent paleoenvironmental study relying on sediment proxies. Physical properties of whole-round sediment cores are acquired as a first step of sediment core description, prior to slicing of sediment cores into two halves. Here, we present processed physical-properties data of core MSM31_561-2_GKG acquired with a Geotek MSCL-S system on the unsplit core, retrieved during RV Maria S. Merian expedition MSM31 from the Yermak Plateau in summer 2013. Cores were processed according to the standard protocol given by the manufacturer Geotek Ltd.